Screening of various parts of Phaleria macrocarpa plant for α-glucosidase inhibitory activity - E., Sabina; I. S., M. Zaidul; Ghafoor, Kashif; M. Jaffri, J.; F., Sahena; Babiker, E. E.; Perumal, V.; Mirhosseini, Hamed; Mehrnoush, Amid; A., Khatib (Wiley-Blackwell Publishing, 2016)
Phaleria macrocarpa is an herbal plant used in Malaysia to enhance vitality. The aim of this study was to screen the α-glucosidase inhibitory activity of different parts (fruit flesh, leaves and stem) of P. macrocarpa. Methanol (polar) and n-hexane (nonpolar) extracts, obtained by room temperature solvent extraction, were evaluated for in vitro α-glucosidase activity inhibition. The compounds were identified by using gas chromatography-mass spectrometry (GC-MS) according to their similarity index of >70%, which might be responsible for α-glucosidase inhibitory activity. The methanol extract of the fruit flesh had the highest yield (25.6 ± 0.5%), whereas the n-hexane extract of the stem is more effective against α-glucosidase activity (IC50 0.8 ± 0.1 μg/mL). The fruit flesh (IC501.3 ± 0.2 μg/mL) and leaves (IC501.6 ± 0.6 μg/mL) had also well effectively. The identified metabolites are predominantly phenolics, carbohydrates, triterpenes and organic acids, such as D-fructose, squalene, α-linolenic acid and α-D-glucopyranoside. In-depth chemical profiling using GC-MS was performed for the first time for this plant to assess the likely compounds present in the extract that could be associated with anti-hyperglycemic activity. Of the three parts tested, every part indicates the potential α-glucosidase inhibitory activity and hexane extract of stem showed more inhibitory activity among all extracts. Thus, P. macrocarpa can attenuate hyperglycemia by potently inhibiting carbohydrate hydrolyzing enzymes, making it a viable plant as a source of natural compounds for the management of type 2 diabetes mellitus.